Lithium-ion capacitor
Patent Information
- Application Number
- JP2023143940
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2015-07-10
- Filing Date
- 2023-09-05
- Publication Date
- 2025-03-05
- Estimated Expiration
- 2035-10-16
AI Technical Summary
【0011】 本発明のリチウムイオンキャパシタによれば、85℃の高温環境において、容量を維持することができ、且つ内部抵抗の増加を小さく抑えることができる。
Smart Images

Figure 0007639862000012 
Figure 0007639862000013 
Figure 0007639862000014
Abstract
Description
[Technical field]
[0001] The present invention relates to a lithium ion capacitor. [Background technology]
[0002] Lithium ion capacitors are so-called hybrid capacitors, and typically, an electrode that physically adsorbs and desorbs ions, with an active material such as activated carbon held in a current collecting foil, is used as the positive electrode, and an electrode that absorbs and desorbs lithium ions by an oxidation-reduction reaction is used as the negative electrode. Lithium ion capacitors are expected to be used in a variety of applications as electricity storage devices that can achieve both large capacity and high output, and for example, in-vehicle applications are being considered.
[0003] In this regard, Patent Document 1 discloses an electrode binder for binding an active material to a current collector foil, taking into consideration the development of batteries including capacitors for in-vehicle use, although the invention is focused on lithium ion batteries rather than lithium ion capacitors. Styrene-butadiene rubber (SBR), which has been conventionally used as an electrode binder, is a water-based binder, which is desirable in that it is easy to reduce the environmental load in the electrode manufacturing process. In response to this, Patent Document 1 points out the problem of oxidative deterioration when SBR is used in the positive electrode of a lithium ion battery, and claims that an aqueous binder containing a polymer with a highly crosslinked structure that includes a specific structural unit derived from a monomer having a hydroxyl group and a specific structural unit derived from a polyfunctional (meth)acrylate monomer will not cause oxidative deterioration and will not affect performance even in a relatively high temperature usage environment of 60°C. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] JP 2014-160638 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, in the case of in-vehicle use of lithium ion capacitors, a higher temperature environment is assumed, and durability at 85°C is a guideline even when installed in a vehicle cabin. In contrast, the electrode binder in Patent Document 1 is assumed to be used in a high-temperature environment of 60°C, and durability at 85°C is not guaranteed when this electrode binder is applied to a lithium ion capacitor. In addition, PEO·PEG (a mixture of polyethylene oxide and polyethylene glycol) and acrylic thermoplastic elastomers are also examples of aqueous binders used in electrodes, but the binding strength of both of them decreases in a high-temperature environment of 85°C. It has been confirmed that when these are used as binders for the positive electrode of a lithium ion capacitor, the resistance derived from the positive electrode increases significantly.
[0006] In addition, in a high-temperature environment of 85°C, the electrolyte is also affected by heat, but Patent Document 1 focuses only on the electrode binder and does not consider the durability of the electrolyte. Therefore, Patent Document 1 states that a lithium salt compound generally used in lithium-ion batteries can be used as the electrolyte, and lithium hexafluorophosphate is used in a specific example. However, it was found that a lithium-ion capacitor using lithium fluorophosphate as an electrolyte cannot be used in a high-temperature environment of 85°C because the capacity is significantly reduced and the internal resistance is significantly increased.
[0007] Therefore, an object of the present invention is to provide a lithium ion capacitor that can maintain its capacity in a high-temperature environment of 85° C. and that exhibits a small increase in internal resistance. [Means for solving the problem]
[0008] The present invention provides a lithium ion capacitor having a positive electrode, a negative electrode, and an electrolyte in contact with the positive electrode and the negative electrode, the electrolyte containing an organic solvent and a lithium salt electrolyte having an imide structure, the concentration of the lithium salt having an imide structure being 0.5 mol / L or more and 10 mol / L or less, the positive electrode having a current collector foil and a positive electrode active material, the positive electrode active material being held by the current collector foil via a binder containing a polymer having a Hansen solubility parameter RED value of greater than 1 at 60°C in the electrolyte. The RED value is expressed as Ra / R0, where Ra is the distance between the Hansen solubility parameter of the polymer and the Hansen solubility parameter of the electrolyte, and R0 is the interaction radius, which is the radius of the polymer's dissolution sphere. The Hansen solubility parameter and interaction radius of the polymer are calculated by mixing the polymer with each of a plurality of solvents whose Hansen solubility parameters are known, and plotting the Hansen solubility parameters of the solvents in which the polymer dissolves and the solvents in which the polymer does not dissolve in the Hansen space, and the solvents in which the polymer dissolves and the solvents in which the polymer does not dissolve are distinguished based on the shape change of the mixed polymer at room temperature, and further, when no difference in the shape change is observed at room temperature, the solvents in which the polymer dissolves and the solvents in which the polymer does not dissolve are distinguished based on the shape change at 60°C. It is a lithium ion capacitor.
[0009] The polymer is preferably polyacrylic acid.
[0010] The organic solvent does not contain dimethyl carbonate and contains ethylene carbonate and propylene carbonate, and the ethylene carbonate is contained in a larger amount than the propylene carbonate. Effect of the Invention
[0011] According to the lithium ion capacitor of the present invention, the capacity can be maintained in a high-temperature environment of 85° C., and an increase in internal resistance can be suppressed to a small extent. [Brief description of the drawings]
[0012] [Figure 1] FIG. 2 is a diagram showing the Hansen solubility parameters of an electrolyte and a polymer contained in a binder in a Hansen space. [Diagram 2] FIG. 1 is a diagram illustrating a method for determining a dissolved sphere of a polymer contained in a binder. [Diagram 3] 1 is a graph showing the capacity retention rate of a lithium ion capacitor after being left in a high-temperature (85° C.) environment. [Figure 4] 1 is a graph showing the internal resistance increase rate of a lithium ion capacitor after being left in a high temperature (85° C.) environment. [Diagram 5] 1 is a graph showing the relationship between the content ratio of cyclic carbonate in an organic solvent and ionic conductivity. [Figure 6] 1 is a graph showing the relationship between the content ratio of cyclic carbonate in an organic solvent not containing dimethyl carbonate and ionic conductivity. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0013] [Main components of lithium ion capacitors] The lithium ion capacitor of the present invention has at least a positive electrode, a negative electrode, and an electrolyte in contact with the positive electrode and the negative electrode.
[0014] [Electrolyte] The electrolytic solution includes a solvent and an electrolyte.
[0015] <Solvent> As the solvent, an organic solvent that has been used in the lithium ion capacitor is used, and examples of this type of organic solvent include carbonate organic solvents, nitrile organic solvents, lactone organic solvents, ether organic solvents, alcohol organic solvents, ester organic solvents, amide organic solvents, sulfone organic solvents, ketone organic solvents, and aromatic organic solvents. The solvent can be used by mixing one or more kinds in an appropriate composition ratio. Examples of the carbonate organic solvent include cyclic carbonates such as ethylene carbonate (EC), propylene carbonate (PC), and fluoroethylene carbonate (FEC), and chain carbonates such as ethyl methyl carbonate (EMC), diethyl carbonate (DEC), and dimethyl carbonate (DMC).
[0016] Examples of nitrile organic solvents include acetonitrile, acrylonitrile, adiponitrile, valeronitrile, and isobutyronitrile. Examples of lactone organic solvents include γ-butyrolactone and γ-valerolactone. Examples of ether organic solvents include cyclic ethers such as tetrahydrofuran and dioxane, and chain ethers such as 1,2-dimethoxyethane, dimethyl ether, and triglyme. Examples of alcohol organic solvents include ethyl alcohol and ethylene glycol. Examples of ester organic solvents include phosphate esters such as methyl acetate, propyl acetate, and trimethyl phosphate, sulfate esters such as dimethyl sulfate, and sulfite esters such as dimethyl sulfite. Examples of amide organic solvents include N-methyl-2-pyrrolidone and ethylenediamine. Examples of sulfone organic solvents include chain sulfones such as dimethyl sulfone, and cyclic sulfones such as 3-sulfolene. Examples of ketone organic solvents include methyl ethyl ketone, and examples of aromatic organic solvents include toluene. The above-mentioned various organic solvents, excluding the carbonate-based organic solvents, are preferably used in combination with a cyclic carbonate (particularly ethylene carbonate (EC)), and are expected to be used, for example, as a replacement for the chain carbonate described below.
[0017] In the electrolyte of a lithium ion capacitor, it is preferable to use a carbonate-based organic solvent having excellent oxidation resistance, taking into consideration the available voltage range (for example, about +4.0V based on Li). Furthermore, it is preferable that the electrolyte has high ionic conductivity (S / m, S: Siemens, m: meters), which is an index of internal resistance, and this ionic conductivity can be improved by lowering the viscosity of the electrolyte and increasing the degree of dissociation of the electrolyte (described later). For this reason, it is even more preferable to use a carbonate-based organic solvent obtained by mixing a cyclic carbonate, which increases the degree of dissociation of the electrolyte, with a low-viscosity chain carbonate as the organic solvent (see Table 6 below).
[0018] Here, various chain carbonates can be used as the chain carbonate, but from the viewpoint of improving the heat resistance of the electrolyte, it is preferable not to use dimethyl carbonate (DMC) which has a low boiling point and poor heat resistance (see Table 6 below). That is, when dimethyl carbonate (DMC) is contained in the organic solvent, dimethyl carbonate (DMC) is thermally decomposed to diethyl carbonate (DEC), and there is a concern that the decomposition by-product at that time will cause an increase in internal resistance and a deterioration in heat resistance (this speculation does not limit the present invention). And, considering that the lithium ion capacitor will be used in a high temperature environment, it is preferable to use ethyl methyl carbonate (EMC) which has a relatively high boiling point and low viscosity, or diethyl carbonate (DEC) which has an even higher boiling point, as the chain carbonate. And, from the viewpoint of improving both the ionic conductivity and heat resistance of the electrolyte, it is even more preferable to use a mixture of ethyl methyl carbonate (EMC) and diethyl carbonate (DEC). The ratio of ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) in the organic solvent is not particularly limited, but can be set within the range of EMC:DEC=2:1 to 1:2, for example.
[0019] In addition, various cyclic carbonates can be used as the cyclic carbonate, but from the viewpoint of improving the oxidation resistance of the electrolyte, it is preferable to use ethylene carbonate (EC) that has the ability to generate a solid electrolyte interphase (SEI) film. When ethylene carbonate (EC) and other cyclic carbonates (e.g. PC) are mixed as the cyclic carbonate, it is preferable to contain more ethylene carbonate (EC) than other cyclic carbonates (e.g. PC). By containing a relatively large amount of ethylene carbonate (EC) in this way, its SEI film generation ability is suitably exerted, and after ethylene carbonate (EC) is reductively decomposed, a protective film called SEI is formed on the negative electrode surface, and the electrolyte is not directly exposed to the potential of lithium (Li).
[0020] Considering that the lithium ion capacitor is used in a low-temperature environment, it is desirable that the electrolyte solidification and the solvent components do not occur as much as possible in a low-temperature environment of about -40°C. For this reason, when ethylene carbonate (EC) with a high melting point is used as the cyclic carbonate, it is preferable that the ratio of ethylene carbonate (EC) to the total amount of the organic solvent is less than 35 vol%. By using a mixture of propylene carbonate (PC) with a low melting point and ethylene carbonate (EC), the content of the cyclic carbonate in the organic solvent can be increased without causing the electrolyte solidification and the solvent components to precipitate as much as possible. In this case, the total ratio of ethylene carbonate (EC) and propylene carbonate (PC) to the total amount of the organic solvent is preferably less than 55 vol%, more preferably less than 40 vol%. If the total ratio of ethylene carbonate (EC) and propylene carbonate (PC) is 55 vol% or more, the possibility of the electrolyte solidification and the solvent components to precipitate in a low-temperature environment increases extremely. Furthermore, if the total ratio of ethylene carbonate (EC) and propylene carbonate (PC) is 40 vol% or more, the desired ion conductivity may not be obtained, for example, in a low temperature environment. When ethylene carbonate (EC) and propylene carbonate (PC) are mixed and used, the total ratio of these to the total amount of organic solvents is set to the range of 35 vol% to 20 vol%, so that the desired ion conductivity can be obtained in a wide temperature range (for example, 25°C to -40°C) without causing solidification of the electrolyte or precipitation of the solvent components.
[0021] <Electrolytes> The electrolyte is ionized into lithium ions and anions to contribute to the charge / discharge reaction, and mainly contains lithium salts having an imide structure. Examples of lithium salts having an imide structure include lithium bis(fluorosulfonyl)imide [LiFSI], lithium bis(trifluoromethanesulfonyl)imide [LiTFSI], and lithium bis(pentafluoroethanesulfonyl)imide [LiBETI]. The lithium salts having an imide structure may be used alone or in combination with one or more other types. In addition, other lithium salt electrolytes may be used in combination within a range that does not impair the effects of the present invention. The electrolyte is preferably contained in the electrolytic solution at 0.5 to 10.0 mol / L. If the concentration of the electrolyte is less than 0.5 mol / L, the ion conductivity is likely to decrease due to insufficient ion concentration. On the other hand, if the concentration of the electrolyte exceeds 10.0 mol / L, the viscosity of the electrolytic solution increases, and the ion conductivity is likely to decrease. More preferably, the concentration of the electrolyte is 0.5 to 2.0 mol / L. In this case, the viscosity of the electrolytic solution is optimal, and the ion conductivity is unlikely to decrease.
[0022] The electrolyte may contain additives as appropriate. Examples of the additives include vinylene carbonate (VC) and fluoroethylene carbonate (FEC).
[0023] [Positive electrode] In the positive electrode, an electric double layer is formed by physical adsorption and desorption of ions during charging and discharging. The positive electrode includes at least a current collector foil, a positive electrode active material, and a binder, and may include a conductive assistant as necessary. The positive electrode is configured such that the positive electrode active material and the like are held on the current collector foil via the binder.
[0024] <Current collecting foil> As the current collecting foil, any foil that has been used in a conventional lithium ion capacitor can be used, for example, a perforated conductive metal foil such as aluminum or stainless steel.
[0025] <Cathode active material> The positive electrode active material may be particles with a large specific surface area capable of absorbing and desorbing ions, such as activated carbon or carbon nanotubes.
[0026] <Binder> The binder is used to bind the materials constituting the positive electrode. The binder is mainly composed of a polymer, which is an adhesive component. The polymer has a RED value (relative energy difference) based on the Hansen solubility parameter (HSP) in the electrolyte solution that is greater than 1. An example of such a polymer is polyacrylic acid. Here, polyacrylic acid is a broad concept that includes not only unneutralized polyacrylic acid but also neutralized salts and crosslinked polyacrylic acid. Polyacrylic acid may be used alone or in combination of two or more types. Water or an organic solvent may be used as a solvent for dissolving the polymer. Aqueous binders using water as a solvent are preferred because they can reduce the environmental load during the manufacturing process. Polyacrylic acid is also suitable in that it can be used to form an aqueous binder using water as a solvent.
[0027] The Hansen solubility parameter was announced by Charles M Hansen, and is known as an index of the solubility of substances with each other. The Hansen solubility parameter is composed of the following three values, D, P, and H, and these three parameters are expressed as coordinates in a three-dimensional space (Hansen space). In Figure 1, the Hansen solubility parameter of the polymer is indicated by the symbol a, and the Hansen solubility parameter of the electrolyte is indicated by the symbol b in the Hansen space. D: (atomic) dispersion force P: (molecular) polarizability H: Hydrogen bonding strength (of molecules) The solubility of two substances is estimated based on the distance between the coordinates indicating the Hansen solubility parameters of each substance; the closer the coordinates are to each other, the easier the substance is to dissolve, and the farther apart the substance is, the harder it is to dissolve.
[0028] The Hansen solubility parameters of an electrolyte can be calculated from the chemical structure and composition ratio of the components. In this case, they can be obtained using the software HSPiP (Hansen Solubility Parameters in Practice: Windows (registered trademark) software for efficiently handling HSP) developed by Hansen et al.
[0029] To calculate the Hansen solubility parameter of a polymer, the polymer is dissolved (mixed) in multiple solvents with known Hansen solubility parameters, and the Hansen solubility parameters of the solvents in which the polymer dissolves and the solvents in which it does not dissolve are plotted in Hansen space. The center of the sphere (Hansen's solubility sphere) formed by the collection of plots of the solvents in which the polymer dissolves is taken as the Hansen solubility parameter of the polymer. The solubility sphere and Hansen solubility parameter of the polymer can also be calculated using the software HSPiP. Figure 2 shows an example in which polyacrylic acid (sodium neutral salt of polyacrylic acid) is used as the polymer, with the Hansen solubility parameters of the solvents in which polyacrylic acid dissolves shown as black circles, the Hansen solubility parameters of the solvents in which it does not dissolve shown as black squares, and the calculated solubility sphere s shown. The coordinates of the center of the solubility sphere s shown as a white circle are taken as the Hansen solubility parameter a of the polymer.
[0030] The RED value of a polymer for an electrolyte is expressed as RED=Ra / R0, where Ra is the distance between the Hansen solubility parameter of the polymer and the Hansen solubility parameter of the electrolyte, and R0 is the interaction radius, which is the radius of the polymer's dissolution sphere. When the RED value of a polymer for an electrolyte is greater than 1, as shown in Figure 1, the Hansen solubility parameter b of the electrolyte is located outside the polymer's dissolution sphere s, and the electrolyte and the polymer are difficult to dissolve in each other. In addition, Figure 1 shows the Hansen solubility parameter of an electrolyte containing 1 mol / L of lithium bis(fluorosulfonylimide) (LiFSI) in a mixed solvent of 30 vol% ethylene carbonate (EC), 30 vol% dimethyl carbonate (DMC), and 40 vol% ethyl methyl carbonate (EMC).
[0031] The binder is preferably added in an amount of 1 to 10% by mass relative to the positive electrode active material. If the amount is less than 1% by mass, the binding force is likely to be insufficient, whereas if the amount is more than 10% by mass, this may cause an increase in conductor resistance.
[0032] <Conductive additive> The conductive additive can be appropriately added to reduce the conductor resistance inside the positive electrode and at the interface of the current collector foil. As the conductive additive, those conventionally used in lithium ion capacitors can be used, such as acetylene black, graphite fine particles, fine fibers, etc.
[0033] <How to make the positive electrode> The positive electrode is produced by applying a positive electrode slurry, which is a mixture of other constituent materials and water as a solvent, to a current collector foil to form a coating. If the thickening effect of the binder in the positive electrode slurry is insufficient, a thickener such as carboxycellulose can be added as appropriate. In that case, the total amount of the binder and thickener added is preferably 1 to 10 mass% relative to the positive electrode active material. The water solvent is used when the viscosity of the slurry is measured using a B-type viscometer, and the viscosity is 2s -1 It is preferable to adjust the amount added so that the measured value is in the range of 1000 to 10000 mPa·s, as this makes it easier to form a coating on the current collector foil.
[0034] [Negative electrode] In the negative electrode, the absorption and desorption of lithium ions occurs during charging and discharging. The negative electrode can be a negative electrode constituting a conventional lithium ion capacitor. Typically, a negative electrode active material such as graphite capable of absorbing and desorbing lithium ions is held on a current collector foil via a binder. Examples of the current collector foil for the negative electrode include copper, aluminum, and stainless steel. Although a binder that has been conventionally used can be used, from the viewpoint of environmental conservation, it is preferable to use a water-based binder such as styrene-butadiene rubber (SBR).
[0035] [Configuration of lithium ion capacitor] The lithium ion capacitor of the present invention can have a cell configuration similar to that of a conventional lithium ion capacitor, for example, a stacked cell in which a positive electrode and a negative electrode are stacked with a separator therebetween, or a wound cell in which a separator is interposed between a positive electrode and a negative electrode and the electrodes are wound.
[0036] The amount of the slurry for the positive and negative electrodes to be applied in the above-mentioned embodiment is adjusted depending on the discharge capacity, the size of the positive and negative electrodes, etc. The thickness of the current collector foil is adjusted depending on the internal resistance performance of the lithium ion capacitor so that the current collector foil is not damaged during manufacturing. The solvent is changed depending on the performance of the lithium ion capacitor. EXAMPLES
[0037] [Creating the positive electrode] First, using activated carbon powder as the positive electrode active material, polyacrylic acid (sodium neutralized salt of polyacrylic acid), acrylic acid ester or styrene-butadiene rubber (SBR) as the binder, acetylene black as the conductive assistant, carboxymethyl cellulose (CMC) as the thickener, and water as the solvent, positive electrode slurries A to C containing the positive electrode active material were prepared with the compositions shown in Table 1. In Table 1, "parts" indicates parts by mass and "%" indicates % by mass.
[0038] [Table 1]
[0039] A positive electrode slurry A using polyacrylic acid as a binder was prepared by the following procedure. (1) All the materials and water were mixed in a mixer a (Thinky Mixer ARE-310) to prepare a press slurry. (2) The pressed slurry obtained in (1) was further mixed in a mixer b (Filmix 40-L, manufactured by Primix Corporation) to prepare an intermediate slurry. (3) The intermediate slurry obtained in (2) was mixed again in the mixer a to prepare a positive electrode slurry A.
[0040] Positive electrode slurries B and C using acrylic ester or SBR as the binder were prepared by the following procedure. (1) Materials other than the binder and water were mixed in a mixer a to prepare a press slurry. (2) The pressed slurry obtained in (1) was further mixed in a mixer b to prepare an intermediate slurry. (3) A binder was added to the intermediate slurry obtained in (2) and mixed in a mixer a to prepare a positive electrode slurry B or C.
[0041] Next, a 15 μm-thick aluminum foil (porous foil) was used as a current collector foil, and the positive electrode slurries A to C were applied to the current collector foil and dried to prepare positive electrodes A to C. The amount of the positive electrode slurry applied was set so that the mass of the activated carbon after drying was 3 mg / cm. 2 The positive electrode slurry was applied to the current collector foil using a blade coater or a die coater.
[0042] [Creating the negative electrode] First, 95 parts by mass of graphite as the negative electrode active material, 1 part by mass of SBR as a binder, 1 part by mass of CMC as a thickener, and 100 parts by mass of water as a solvent were mixed together to prepare a negative electrode slurry by the following procedure. (1) Materials other than the binder and water were mixed in a mixer a to prepare a press slurry. (2) The pressed slurry obtained in (1) was further mixed in a mixer b to prepare an intermediate slurry. (3) A binder was added to the intermediate slurry obtained in (2), and the mixture was mixed in a mixer a to prepare a negative electrode slurry.
[0043] Next, a 10 μm thick copper foil (porous foil) was used as a current collector, and the negative electrode slurry was applied to the current collector and dried to prepare a negative electrode. The amount of the negative electrode slurry applied was set so that the mass of the graphite after drying was 3 mg / cm. 2 The negative electrode slurry was applied to the current collector foil using a blade coater.
[0044] [Adjustment of electrolyte] A mixed solvent of 30 vol% ethylene carbonate (EC), 30 vol% dimethyl carbonate (DMC), and 40 vol% ethyl methyl carbonate (EMC) was used as the solvent, and 1 mol / L of lithium bis(fluorosulfonylimide) (LiFSI) was added to the mixed solvent to prepare electrolyte I. In addition, lithium hexafluorophosphate (LiPF6) was added to the mixed solvent to prepare electrolyte P. In addition, ethylene carbonate (EC) 20 Electrolyte I2 was prepared by adding 1 mol / L of lithium bis(fluorosulfonylimide) (LiFSI) to a mixed solvent of 46.7 vol% ethyl methyl carbonate (EMC), 23.3 vol% diethyl carbonate (DEC), and 10 vol% propylene carbonate (PC).
[0045] [Preparation of lithium ion capacitor cells for evaluation] Lithium ion capacitor cells for evaluation in the examples and comparative examples were fabricated using the combinations of positive electrodes and electrolytes shown in Table 2 according to the following procedure. (1) The positive and negative electrodes were each punched out to form a rectangle measuring 60 mm x 40 mm. The coating film on a 20 mm x 40 mm area on one end of the long side was peeled off, leaving a 40 mm x 40 mm area of the coating film, and a current collecting tab was attached. (2) A laminate was prepared by placing the coating film portions of the positive and negative electrodes facing each other with a 20 μm thick cellulose separator interposed therebetween. (3) The laminate produced in (2) and a metallic lithium foil for lithium pre-doping were enclosed in an aluminum laminate foil, an electrolyte was injected, and the resultant was sealed to produce a lithium ion capacitor cell for evaluation.
[0046] [Table 2]
[0047] [Initial performance measurements] For each of the prepared lithium ion capacitor cells for evaluation, lithium pre-doping, charging / discharging, and aging were performed, and then the internal resistance and discharge capacity were measured at room temperature (25°C) with a cutoff voltage of 2.2 to 3.8 V and a measurement current of 10 C, and the results were regarded as the initial performance.
[0048] [Durability test (85℃ float test)] The evaluation lithium ion capacitor cell was left in a thermostatic chamber at 85°C while the voltage was held at 3.8V by connecting an external power source. The time of leaving the cell corresponds to the 85°C, 3.8V float time. After a predetermined time, the evaluation lithium ion capacitor cell was removed from the thermostatic chamber and returned to room temperature. The internal resistance and discharge capacity were measured under the same conditions as those for the measurement of the initial performance, and the capacity retention rate (percentage of discharge capacity when the initial discharge capacity is taken as 100%) and the internal resistance increase rate (rate of increase in internal resistance from the initial performance) were calculated. The results are shown in Table 3 and Figures 3 and 4.
[0049] [Table 3]
[0050] As shown in FIG. 3 and the like, when left in a high-temperature environment of 85°C, the capacity retention rate was halved in a short time in Comparative Example 3, which used an electrolyte solution containing lithium fluorophosphate without an imide structure as the electrolyte, whereas the capacity retention rate was kept high for a long time in Example 1, Example 2, Comparative Example 1, and Comparative Example 2, which used an electrolyte solution containing a lithium salt having an imide structure as the electrolyte. However, as shown in FIG. 4 and the like, even when an electrolyte solution containing a lithium salt having an imide structure as the electrolyte was used, it was revealed that there was a difference in the internal resistance increase rate depending on the composition of the binder of the positive electrode. Then, the RED value (see Table 2) of the polymer constituting the binder of the positive electrode with respect to the electrolyte was compared, and it was found that the internal resistance increase rate was high in Comparative Example 1, which used an acrylic acid ester with a RED value of 1 or less, and Comparative Example 2, which used SBR. In contrast, in Examples 1 and 2, an electrolyte solution containing a lithium salt having an imide structure as the electrolyte was used, and polyacrylic acid with a RED value of more than 1 with respect to the electrolyte was used as the polymer constituting the binder of the positive electrode. In this case, it was revealed that the polymer constituting the binder of the positive electrode is difficult to dissolve in the electrolyte, and even when left in a high-temperature environment of 85°C, the capacity retention rate is kept high and the internal resistance increase rate is suppressed to a small value. In particular, in Example 2, it was found that the internal resistance increase rate is further suppressed to a small value. It was easily inferred that the result of Example 2 is due to the fact that the carbonate-based organic solvent as the organic solvent does not contain dimethyl carbonate (DMC) and contains more ethylene carbonate (EC) than propylene carbonate (PC). In order to calculate the RED value, the calculation of the Hansen solubility parameter and interaction radius of the polymer and the calculation of the Hansen solubility parameter of the electrolyte were performed according to the following procedure.
[0051] Calculation of Hansen solubility parameters and interaction radius of polymers For each binder, the polymer interaction radius R0 and the Hansen solubility parameter were calculated using the following procedure. (1) Preparation of test samples A binder dissolved in water is dropped onto a Teflon sheet (Teflon: registered trademark) and dried at 60° C. for at least one day to prepare a test sample. (2) Preparation of test solvent Test solvents No. 1 to 29 were prepared with the compositions shown in Table 4. Each prepared test solvent was placed in a 10 ml vial, and molecular sieves 3A were also added to highly hygroscopic solvents. (3) Swelling test The test samples were immersed in each test solvent. They were left at room temperature for 1 to 14 days, and the changes in the shape of the samples were observed. If no difference was observed in the change in shape (degree of swelling) due to the test solvent, they were left at 60°C. (4) Evaluation of shape change After (3), the change in shape of the test sample in each test solvent was judged and scored into the following four levels: 0: No change, 1: Dissolution, 2: Swelling, 3: Other changes (discoloration, etc.) (5) Calculation of Hansen solubility parameter and interaction radius Using the software HSPiP, the Hansen solubility parameters and interaction radii were calculated based on the evaluation results of (4). The results are shown in Table 5.
[0052] [Table 4]
[0053] [Table 5]
[0054] Calculation of Hansen solubility parameters of electrolytes The Hansen solubility parameters of electrolyte I were calculated using the software HSPiP based on the chemical structure and composition ratio of the components. The Hansen solubility parameters of electrolyte I were D: 16.3, P: 12.5, and H: 7.5.
[0055] Effects of organic solvents The following [Table 6] shows the physical properties of various solvent components used as carbonate-based organic solvents. [Table 7] to [Table 9] show the properties of various electrolyte solutions in which 1 mol / L LiFSI has been added to various carbonate-based organic solvents (boiling point (a method for measuring boiling point will be described later), the presence or absence of precipitation in a low-temperature environment (a method for checking the presence or absence of precipitation will be described later), and ionic conductivity in normal and low-temperature environments). In [Table 7], EC was used as the cyclic carbonate, in [Table 8], PC was used as the cyclic carbonate, and in [Table 9], a mixture of EC and PC was used as the cyclic carbonate. [Table 10] and [Table 11] show the properties of various electrolyte solutions in which 1 mol / L LiFSI has been added to various carbonate-based organic solvents (the presence or absence of precipitation in a -50°C environment). The graph in Fig. 5 was prepared based on Tables 7 to 9, with the horizontal axis showing the content ratio (sufficiency) of the cyclic carbonate relative to the total amount of organic solvent, and the vertical axis showing the ionic conductivity values at room temperature and low temperature. The graph in Fig. 6 was prepared based on Table 9, with the horizontal axis showing the content ratio (sufficiency) of the cyclic carbonate relative to the total amount of organic solvent, and the vertical axis showing the ionic conductivity values at room temperature and low temperature.
[0056] <Method of measuring boiling point> Here, the method of measuring the boiling points of various electrolytes shown in [Table 7] to [Table 9] will be described in detail. In this test, a separator and the like were enclosed in an aluminum laminate foil in an Ar atmosphere, an electrolyte was injected, and the resulting cell was sealed to prepare a lithium ion capacitor cell. The lithium ion capacitor cell was then placed in a thermostatic chamber, and the temperature was raised to a predetermined temperature in 5°C increments, after which the cell was left for about 30 minutes. After leaving the cell for about 30 minutes, the lithium ion capacitor cell was observed, and if the electrolyte exceeded its boiling point, the electrolyte had turned into gas and the lithium ion capacitor cell had swelled. Therefore, in this test, the upper limit temperature at which the lithium ion capacitor cell did not swell was taken as the boiling point of each electrolyte.
[0057] <How to check for precipitation in a low-temperature environment> Next, a method for checking the presence or absence of precipitation in low-temperature environments for various electrolytes shown in [Tables 7] to [Table 11] will be described in detail. In this test, a separator and other components were placed in a transparent container in an Ar atmosphere, an electrolyte was poured into the container, and the container was sealed to prepare a lithium-ion capacitor cell. The lithium-ion capacitor cell was then placed in a thermostatic chamber and left for 30 minutes at a specified temperature. After leaving the cell for 30 minutes, the lithium-ion capacitor cell was observed, and precipitation was deemed to have occurred when it was no longer transparent (when it became cloudy or solidified).
[0058] [Table 6]
[0059] [Table 7]
[0060] [Table 8]
[0061] [Table 9]
[0062] [Table 10]
[0063] [Table 11]
[0064] With reference to [Table 7] and [Table 8], it was found that the boiling point of the electrolyte solution is lowered by including dimethyl carbonate (DMC) in the organic solvent. From this, it was easily inferred that the use of dimethyl carbonate (DMC) as the organic solvent is likely to cause an increase in the internal resistance of the electrolyte solution and a deterioration in heat resistance (this inference does not limit the present invention). Also, with reference to [Table 7] to [Table 9], it was found that the boiling point of the electrolyte solution is raised by including ethyl methyl carbonate (EMC) or diethyl carbonate (DEC) in the electrolyte solution instead of dimethyl carbonate (DMC). From this, it was found that it is preferable to use ethyl methyl carbonate (EMC) or diethyl carbonate (DEC) as the chain carbonate, considering that the lithium ion capacitor is used in a high temperature environment. Furthermore, it was found that it is more preferable to use a mixture of ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) from the viewpoint of improving both the ionic conductivity and heat resistance of the electrolyte solution.
[0065] In addition, referring to Table 10, precipitation of solvent components was observed in an electrolytic solution of an organic solvent containing 35 vol% or more of ethylene carbonate (EC). From this, it was found that when ethylene carbonate (EC) is used as a cyclic carbonate, it is preferable to set the ratio of ethylene carbonate (EC) in the organic solvent to less than 35 vol%.
[0066] Also, referring to [Table 11], it was found that the content of cyclic carbonate in the organic solvent can be increased without causing solidification of the electrolyte or precipitation of the solvent components as much as possible by using a mixture of propylene carbonate (PC) and ethylene carbonate (EC). Also, the electrolyte of the organic solvent containing ethylene carbonate (EC) and propylene carbonate (PC) in a total of 55 vol% or more was extremely likely to solidify. Furthermore, referring to Figures 5 and 6, the electrolyte of the organic solvent containing ethylene carbonate (EC) and propylene carbonate (PC) in a total of 40 vol% or more tended to have a decreased ionic conductivity in a low temperature environment. From this, it was found that the total ratio of ethylene carbonate (EC) and propylene carbonate (PC) to the total amount of the organic solvent is preferably less than 55 vol%, and more preferably less than 40 vol%. It was also found that by setting the combined ratio of ethylene carbonate (EC) and propylene carbonate (PC) to the total amount of organic solvents in the range of 35 vol% to 20 vol%, it is possible to obtain the desired ionic conductivity over a wide temperature range (for example, 25°C to -40°C) while minimizing the occurrence of solidification of the electrolyte.
Claims
1. A lithium ion capacitor having a positive electrode, a negative electrode, and an electrolyte in contact with the positive electrode and the negative electrode, the electrolytic solution includes an organic solvent and a lithium salt electrolyte having an imide structure, the concentration of the lithium salt having an imide structure being 0.5 mol / L or more and 10 mol / L or less; the positive electrode has a current collector foil and a positive electrode active material, the positive electrode active material being held on the current collector foil via a binder containing a polymer having a Hansen solubility parameter RED value of greater than 1 in the electrolyte at 60° C.; The RED value is expressed as Ra / R0, where Ra is the distance between the Hansen solubility parameter of the polymer and the Hansen solubility parameter of the electrolyte, and R0 is the interaction radius, which is the radius of the polymer's dissolution sphere; The Hansen solubility parameter and interaction radius of the polymer are calculated by mixing the polymer in each of a plurality of solvents having known Hansen solubility parameters, and plotting the Hansen solubility parameters of the solvents in which the polymer dissolves and the solvents in which the polymer does not dissolve in Hansen space, and the solvents in which the polymer dissolves and the solvents in which the polymer does not dissolve are distinguished based on a shape change of the mixed polymer at room temperature, and further, when no difference in shape change is observed at room temperature, the solvents in which the polymer dissolves and the solvents in which the polymer does not dissolve are distinguished based on a shape change at 60°C.
2. The lithium ion capacitor according to claim 1, The lithium ion capacitor, wherein the polymer is polyacrylic acid.
3. The lithium ion capacitor according to claim 1 or 2, The organic solvent does not contain dimethyl carbonate and contains ethylene carbonate and propylene carbonate, and the ethylene carbonate is contained in a larger amount than the propylene carbonate.
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery
JP2001076725A
Method of manufacturing electrode for electric double-layer capacitor
JP2009088275A
Composition for electrode, electrode for battery, lithium secondary battery, and method for manufacturing lithium secondary battery
JP2010073335A
Electrochemical cell
JP2012069508A
Nonaqueous electrolytic solution
JP2012216490A